Communication is key: the role of communication in the diffusion of a learning management system into a higher education environment. (1st January 2012) - Beck, Dennis; Black, Erik W.
This paper uses Rogers' diffusion of innovations framework to discuss a communications strategy by which agents of change can educate their peers and decision makers regarding a chosen technology. The strategy examines the role of communications in the knowledge, persuasion, decision, implementation, and confirmation stages of the innovation-decision process. Problems include overstating communication, negative evaluations, and ignoring your audience in your communication with stakeholders. The recommended practices are embracing supportive communication through dedicated employees, a transparent organisational and policy structure, and the increase of resources to the project. It then concludes by proposing a strategy for successful communication during the diffusion process.